Unraveling the regulatory relationship between quorum sensing and the type III secretion system in Yersinia pseudotuberculosis - Slater, Amy (2018)
Yersinia pseudotuberculosis is a mammalian enteropathogen and is the direct ancestor of Y. pestis, the causative agent of the plague. For its pathogenicity, Y. pseudotuberculosis harbours a 70 kb virulence plasmid which encodes the components of the type three secretion system (T3SS) and effector proteins. These effectors serve to evade the host immune system and induce apoptosis of mammalian cells. Consistent with many Gram-negative bacteria, Yersinia facilitate cell: cell signalling through the production and sensing of N-acylhomoserine lactones (AHLs), which functions to mediate the expression of downstream target genes. This cell-cell communication is known as quorum sensing (QS) and is facilitated by two LuxI/R-type systems in Y. pseudotuberculosis: YtbI/R and YpsI/R, and several AHL molecules. Behaviours under QS control include motility, biofilm formation, clumping and the regulation of the T3SS. Recently, QS was reported to repress the T3SS whilst the T3SS attenuated biofilm formation on Caenorhabditis elegans. Colonising both the soil/water environment and the mammalian gut, Y. pseudotuberculosis exhibits a biphasic lifestyle whereby it exerts strict temperature-dependent control over the expression of pYV-encoded genes. The switch between these two lifestyles is govered by a pair of virulence regulators: LcrF is a transcriptional activator that targets pYV-encoded genes and is key for the assembly of the T3SS. Conversely, YmoA is a histone-like protein that represses transcription of lcrF through chromatin compaction. Considering the repression of the T3SS by QS, this study set out to investigate whether this regulation is mediated by a relationship between QS and LcrF/YmoA. By using chromosomal promoter:lux fusions, QS was identified to be an activator of YmoA at both 22oC and 37oC whilst a regulatory relationship between QS and LcrF was also identified. To investigate these links further, AHL profiling of the lcrF and ymoA mutants identified YmoA as a repressor of AHL biosynthesis whilst a very subtle repression was observed in ΔlcrF, suggesting that LcrF may influence AHL synthesis indirectly. Assessing the impact of LcrF and YmoA on the QS-mediated phenotypes of Yop secretion, biofilm formation and motility extended these observations. LcrF had no effect on any of the phenotypes examined supporting the hypothesis of either an indirect mode of regulation, or no regulation at all. In contrast, YmoA influenced both motility and biofilm formation. A decreased motility of ΔymoA was observed on both semi-solid agar and in liquid whereby both the speed and the percentage of motile cells was altered. This suggests an activating role of YmoA on motility. Interestingly, QS is known to repress motility therefore it is likely that YmoA-regulation of motility occurs irrespective of QS. Comparable to that of the QS synthase mutant (ΔypsI/ytbI), biofilm was attenuated in ΔymoA yet restored when cells were cured of the virulence plasmid supporting the hypothesis that the type three-secretion injectisome disrupts biofilm formation. This attenuation of biofilm formation in ΔymoA, in conjunction with the activation of ymoA by QS, led to the hypothesis that the repression of the T3SS by QS works through YmoA. Considering these results, evidence for an interaction between QS and virulence regulators LcrF and YmoA has been confirmed. We propose a model whereby YmoA is the missing link in the QS-mediated repression of the T3SS. Activation of YmoA by QS leads to increased repression of lcrF and subsequently, of the T3SS resulting in the de-repression of this system in the absence of QS.